(untitled) (Journal of Atomic and Molecular Sciences, 2021)
The photodetachment of H^- near a surface is investigated. A laser polarized parallel to the surface is used for the detachment of the electron. Analytical expressions for the detached-electron flux and total photodetachment cross section are derived. The detached electron flux displays strong interference pattern on the screen. Unlike the detached electron flux no visible oscillations are found in the photodetachment cross section. The photodetachment cross section in low energy limits is double of the cross section of H^- in free space.